Giant laryngocele - Santos, Ana Carla Albuquerque dos; Filho, Francisco Januário Farias Pereira; Freitas, Jônatas Catunda de; Rolim, Francieudo Justino; Fernandes, Matheus Augusto Mesquita (Manual Therapy, Posturology & Rehabilitation Journal, 2018)
Laryngocele is an abnormal dilation of the laryngeal saccules arising from the laryngeal ventricle. We report the case of a 50 year-old smoker female patient with a palpable mass in the neck. The laryngoscopy showed a globular mass affecting piriform recess and right hemilarynx, with vocal folds preservation and with semi-occlusion of glottic space. Before performing the computed tomography, the main diagnostic hypothesis was laryngeal neoplasm. Contrasted CT showed an air-filled cavity in topography of cervical level III. The patient was then submitted to resection of the structure.